(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe the knowledge, attitudes, and practices regarding contraceptive methods among first – year nursing students at Tra Vinh University. Subjects and methods: A descriptive cross-sectional study was conducted on 231 first-year nursing students enrolled at Tra Vinh University in 2024. Results: The study was conducted among first-year nursing students, with the majority aged 19 years (96.5%) and 78.8% belonging to the Kinh ethnic group. Overall, 94.4% of students reported being interested in contraceptive methods, and 100% demonstrated knowledge of at least one contraceptive method, including condoms (96.1%), oral contraceptive pills (81%), and intrauterine devices (59.7%). There were 60.6% of students believed that no contraceptive method is completely safe, and 65.4% agreed that contraceptive use is the best option during sexual intercourse; however, they also expressed concerns about the side effects of emergency contraceptive pills. Only 6.1% reported using contraception during their first sexual intercourse. Condoms were the most commonly preferred method (60.7%). Conclusion: First-year nursing students at Tra Vinh University demonstrated good knowledge and attitudes toward contraceptive methods; however, their practical application remains suboptimal. It is therefore necessary to integrate sexuality education and reproductive health education into the curriculum, and to establish student clubs focusing on this topic for students, particularly in medicine and pharmacy-related disciplines.